Design and Fabrication of Low-Cost Tennis Ball Collector Robot - Do, Van Hien (Journal of Technical Education Science, 2025)
Tennis players often practice by hitting many balls from one side of the court to the other when no one else is present, which makes collecting the balls during practice sessions time-consuming. The goal of this research is to design and build a self-driven tennis ball collector that can gather balls from one side of the court, allowing the player to relax instead of physically collecting them. This mechanical tennis ball collector was conceived and developed using a Raspberry Pi controller and Python. Python code was used to locate the tennis balls and measure the distance to obstacles. An Arduino Uno controlled the DC motor's speed and direction. The main structure of this automated tennis ball collector is composed of structural frame materials, facilitating the attachment of all electrical components. Test run results demonstrate that the automatic tennis ball collector, equipped with image detection, can gather a large number of tennis balls on the court within a set time limit.